The Influence of Service Quality and Price Perception on Cunsumer Trust and Revisit Intention at Beauty Care Clinic in Indonesia - Kurnianingrum, Ayu Fitria; Hidayat, Anas (Archives of Business Research, 2020)
A lot of research have been done. These involved variables of service quality, price perception, and trust on revisit intention. However, there are still not many research on these variables investigating consumer behaviors in beauty care clinics. For this reason, this research aims to determine the influence of service quality and price perception on consumer trust and revisit intention of the consumers at beauty care clinics in Indonesia. Survey data were collected from 276 customers of beauty care clinics in Indonesia. Data was analysed using descriptive statistics and partial least square (PLS) path modelling. The result found that service quality had a significant and positive influence on consumer trust, price perception had a significant and positive influence on consumer trust and consumer trust had a significant and positive influence on revisit intention. The novelty of the research was the quality of service and price perception had an important role in building consumer trust that would increase their intention to revisit the beauty care clinic.